DESIGN AND DEVELOPMENT OF T2IG APPLICATION: A NEED ANALYSIS - Mohd Hishamuddin Abdul Rahman; Punithavili Mariappan; Maran Chanthiran; Abu Bakar Ibrahim (Journal of Islamic, Social, Economics and Development, 2022)
This study aims to identify the need of developing an artificial intelligencetechnology educational application. This application is named T2IG, an acronym for Text toInfoGraphics. Meanwhile, the ADDIE and Text Analytics models have been applied to developT2IG applications. The researcher selected 159 Malay language teachers from Penang stateprimary schools. A simple random sampling method was used to determine the number of studysamples in this phase. Quantitative methods using a survey approach were carried out. Thefindings of the descriptive analysis indicate that teachers need the development of thiseducational application. A total of 10 items were listed to identify the development needs of thisapplication. Next, an inferential analysis was conducted to identify differences in the level ofT2IG application development requirements. The t-test and one-way ANOVA findings show nodifference in the level of T2IG application development requirements based on demographicalfactors. Thus, this study can contribute to education by developing an educational applicationwith artificial intelligence elements. Using this application, students will have technologicalinstructional material for learning the Malay language.